KOMPETENSI TENAGA PENJUAL KARTU KREDIT SEBAGA UPAYA MENARIK MINAT NASABAH - Mulyani, Roch (Manajemen & Bisnis Jurnal, 2018)
The concept of competency applied by the Bank Rakyat Indonesia Surakarta Unit has not been well realized in the field of credit card sales at Bank Rakyat Indonesia Surakarta. This is marked by the lack of knowledge about credit card products and its features. The purpose of this study is to analyze and describe the orientation of working smart, Quality Control System, Quality Training System can improve the competence of Bank Rakyat Indonesia Surakarta credit card sales force. The results of the study explain that, the sales force (sales) of Bank Rakyat Indonesia Surakarta. In carrying out their work using orientation works smart. The quality control system at Bank Rakyat Indonesia Surakarta is done by Atasa, who always requests a daily report (credit card customer data) that have been visited. Good quality sales training is the foundation of the success of Bank Rakyat Indonesia Surakarta. In providing salespeople understanding to know more about credit card features. Keywords: Smart Work Orientation, Quality Control System, Quality Training System